2021
DOI: 10.1002/jia2.25741
|View full text |Cite|
|
Sign up to set email alerts
|

Psychosocial interventions for improving engagement in care and health and behavioural outcomes for adolescents and young people living with HIV: a systematic review and meta‐analysis

Abstract: Introduction: Adolescents and young people comprise a growing proportion of new HIV infections globally, yet current approaches do not effectively engage this group, and adolescent HIV-related outcomes are the poorest among all age groups. Providing psychosocial interventions incorporating psychological, social, and/or behavioural approaches offer a potential pathway to improve engagement in care and health and behavioural outcomes among adolescents and young people living with HIV (AYPLHIV). Methods: A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 116 publications
0
25
0
Order By: Relevance
“…Poor HIV treatment outcomes in adolescents and young adults highlight the need for interventions to improve care outcomes in this age group. A recent meta-analysis found that psychosocial interventions for adolescents and young people living with HIV showed small-to-moderate effects on adherence and viral load [49]. Scale-up of successful interventions to improve HIV outcomes of young people living with HIV should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Poor HIV treatment outcomes in adolescents and young adults highlight the need for interventions to improve care outcomes in this age group. A recent meta-analysis found that psychosocial interventions for adolescents and young people living with HIV showed small-to-moderate effects on adherence and viral load [49]. Scale-up of successful interventions to improve HIV outcomes of young people living with HIV should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, administering the RCT also involved a lot of direct face-to-face contact and communication with patients. Interestingly, some RCTs testing out psychosocial interventions did not experience similar challenges because they were able to recruit virtual patients, whereas we were not allowed to do so [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sharing expertise and learning from other research studies who are in a similar situation is important [ 6 ], especially where there is little or varying public health guidelines on continuing research during a pandemic [ 1 ]. Although there are numerous papers reporting on managing clinical trials during the COVID-19 pandemic, there is very little addressing the challenges of conducting an RCT of a psychosocial intervention, which requires direct patient contact in a hospital setting [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review identified 30 randomized controlled trials of psychosocial interventions for adolescents and young adults [ 55 ]; most studies were carried out in the USA (18 studies) or sub-Saharan Africa (9 studies). Psychosocial interventions improved adherence to ART and increased the proportion of individuals with viral suppression.…”
Section: Psychosocial Interventions For Adolescents and Young Adultsmentioning
confidence: 99%